ХРОНОТОП – ЛИРИК КОМПОЗИЦИЯ АСОСИ (Шамшод Абдуллаев шеърлари мисолида) (Scientific journal of the Fergana State University, 2023)
In the article chronotop as the main part of lyrical poetry integrating image, scenery, detail and others is exposed. When poet shifts an artistic world that is in his inner world to the exact place and time, he uses all opportunities of chronotop effectively.